Does entitlement crowd out efficiency or equality seeking? Selling the roles in generosity game experiments - Agnes Bäker; Werner Güth; Kerstin Pull; Manfred Stadler (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
In generosity games, one agreement payoff is exogenously given, whereas the other is endogenously determined by the proposer's choice of the pie size. This has been shown to induce pie choices which are either efficiency or equality seeking. In our experiment, before playing the generosity game, participants are asked to buy their role via a random price mechanism. This should entitle them to exploit the chances which their role provides and at the same time avoid the selection bias of competitive auctions. We find that entitlement crowds out equality seeking and strengthens efficiency seeking. Interpreting participants' willingness to pay as an aspiration level of how much they want to earn, our design further allows us to test for satisficing behavior. Indeed, we find evidence for satisficing behavior in the data.
Keywords: C7; C91; D03; 330; entitlement; generosity; game; efficiency seeking; inequity aversion; satisficing; Spieltheorie; Gerechtigkeit; Wirtschaftliche Effizienz; Crowding out; Test